The Representation of Struggle in the Poem 'Lā tantaẓir aḥadan fa-lan yaʾtī aḥad' by Faruq Juwaidah - Rangkuti, Hamzah Mahmudin; Abshar, Ulil; Hasaniyah, Nur (Universitas Muhammadiyah Yogyakarta, 2026)
The phenomenon of despair and the collapse of heroism in modern Arabic poetry represents a critical response to the socio-political stagnation of the post-Naksa era. This study aims to conduct a profound analysis of the poem